2017
DOI: 10.1007/s11695-017-2810-7
|View full text |Cite
|
Sign up to set email alerts
|

Health and Nutritional Status of Vegetarian Candidates for Bariatric Surgery and Practical Recommendations

Abstract: Vegetarians have comparable health status and nutritional deficiencies, lower iron stores, and higher supplementation use before surgery compared to omnivore LSG candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The BMI information from this study showed a lower prevalence of overweight and obesity when compared to similar self-reported statistics of the general Argentinian population [57,58]. This may be attributed to the high prevalence of individuals with vegetarian dietary patterns in this population, similarly found in other research [38,59,60]. In line with this, our study also reported a lower prevalence of chronic conditions throughout all dietary patterns but particularly in vegetarians as found in similar studies [13,20,61].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The BMI information from this study showed a lower prevalence of overweight and obesity when compared to similar self-reported statistics of the general Argentinian population [57,58]. This may be attributed to the high prevalence of individuals with vegetarian dietary patterns in this population, similarly found in other research [38,59,60]. In line with this, our study also reported a lower prevalence of chronic conditions throughout all dietary patterns but particularly in vegetarians as found in similar studies [13,20,61].…”
Section: Discussionsupporting
confidence: 81%
“…Along with proper nutrition, other lifestyle factors such as water intake, sunlight exposure, and daily exercise have been included in food guides for the promotion of comprehensive healthy lifestyles [36,37]. Although vegans tend to show healthier lifestyle habits than non-vegetarians [7,21,38,39], the avoidance of animal foods is not always accompanied by the adoption of other healthy dietary or lifestyle habits [40]. In fact, recent research shows that it is possible to have unhealthful plant-based diets with increased risk of coronary heart disease [41].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors made recommendations for the dosing of supplements and recommendation on how to avoid potential interactions with other nutrients or medication ( 94 ) . Additionally, Dagan et al proposed nutritional guidelines for vegetarian and vegan patients undergoing bariatric surgery based on their clinical experience and the current knowledge in the field of nutrition in bariatric, vegetarian and vegan patients ( 95 ) . All these different guidelines highlight the heterogeneity in the reporting of bariatric research.…”
Section: Nutritional Recommendations After Bariatric Surgerymentioning
confidence: 99%
“…References of the reviewed study articles in this section: [ 15 , 20 , 34 , 43 , 61 , 62 , 76 , 77 , 78 , 79 , 89 , 93 , 101 , 102 , 108 , 113 , 115 , 116 , 128 , 129 , 136 , 146 , 147 , 150 , 153 ].…”
Section: Discussionmentioning
confidence: 99%